Impact of Coronavirus Disease 2019 in a French Cohort of Myasthenia Gravis. (20th April 2021) - Solé, Guilhem; Mathis, Stéphane; Friedman, Diane; Salort-Campana, Emmanuelle; Tard, Céline; Bouhour, Françoise; Magot, Armelle; Annane, Djillali; Clair, Bernard; Le Masson, Gwendal; Soulages, Antoine; Duval, Fanny; et al.
Abstract : Objective: To describe the clinical characteristics and outcomes of coronavirus disease 2019 (COVID-19) among patients with myasthenia gravis (MG) and identify factors associated with COVID-19 severity in patients with MG. Methods: The CO-MY-COVID registry was a multicenter, retrospective, observational cohort study conducted in neuromuscular referral centers and general hospitals of the FILNEMUS (Filière Neuromusculaire) network (between March 1, 2020, and June 8, 2020), including patients with MG with a confirmed or highly suspected diagnosis of COVID-19. COVID-19 was diagnosed based on a PCR test from a nasopharyngeal swab or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) serology, thoracic CT scan, or typical symptoms. The main outcome was COVID-19 severity based on location of treatment/management (home, hospitalized in a medical unit, or in an intensive care unit). We collected information on demographic variables, general history, and risk factors for severe COVID-19. Multivariate ordinal regression models were used to identify factors associated with severe COVID-19 outcomes. Results: Among 3, 558 patients with MG registered in the French database for rare disorders, 34 (0.96%) had COVID-19. The mean age at COVID-19 onset was 55.0 ± 19.9 years (mean MG duration: 8.5 ± 8.5 years). By the end of the study period, 28 patients recovered from COVID-19, 1 remained affected, and 5 died. Only high Myasthenia Gravis Foundation of America (MGFA) class (≥IV) before COVID-19 was associated with severe COVID-19 ( p = 0.004); factors that were not associated included sex, MG duration, and medium MGFA classes (⩽IIIb). The type of MG treatment had no independent effect on COVID-19 severity. Conclusions: This registry-based cohort study shows that COVID-19 had a limited effect on most patients, and immunosuppressive medications and corticosteroids used for MG management are not risk factors for poorer outcomes. However, the risk of severe COVID-19 is elevated in patients with high MGFA classes (odds ratio, 102.6 [4.4–2, 371.9]). These results are important for establishing evidence-based guidelines for the management of patients with MG during the COVID-19 pandemic.